Determinants on aspects of well-being - Nguyen, Tra Phuong (KDI School, 2001)
The selection of measures for economic development plays an important role for countries to pursue their development goals. Kaushik Basu hypothesized that Per capita income of the poorest 20 percent of the population (Quintile income) should be used in place of Per capita income in evaluating an economy’s performance as the former will correlate more strongly with other indicators of well-being, such as greater life expectation and higher literacy, than does the latter. However, the use of this quintile income will have a great effect on distribution issue and impose important constraints on policy. The transfer from the rich to the poor may raise the income of the poor but, if they reduce savings and capital accumulation by the rich, they may in time lead to lower income in the poorer groups. Thus, the adoption of Basu hypothesis should be put in well consideration. The study performed regression based on a sample of 69 developing countries to empirically test this hypothesis. It found that quintile income in fact does not explain the well-being indicators of life expectancy, infant morality or adult literacy better than per capital income. The hypothesis is not true for all the case but only for middle developing countries. Therefore, policies of other developing countries including Vietnam should focus on social aspect rather than the distribution aspect.
Thesis(Master) --KDI School:Master of Public Policy,2001